The role of probiotics, prebiotics, and postbiotics: cellular and molecular pathways activated on glial cells in Alzheimer’s disease - Aleidy Patricio-Martínez; Aleidy Patricio-Martínez; Felipe Patricio; Felipe Patricio; Edgar Macuil-Chapuli; Edgar Macuil-Chapuli; Enoc Álvaro Martínez-Juárez; Enoc Álvaro Martínez-Juárez; Steven Flores-Díaz; Steven Flores-Díaz; María Lilia Cedillo-Ramírez; Ilhuicamina Daniel Limón (Frontiers in Neuroscience, 2025)
Supplementation with prebiotics and probiotics can modulate the intestinal microbiota, returning it to a more physiological state; therefore, they can be considered as a possible treatment in many prevalent conditions, including neurodegenerative diseases. Alzheimer’s disease (AD) is the most common form of dementia, accounting for 60 to 70% of cases. The neuropathological features of AD include neuritic plaques (extracellular deposits of the beta-amyloid protein, Aβ), neurofibrillary tangles (resulting from hyperphosphorylation of the tau protein), a predominantly cholinergic synaptic decrease, and the presence of inflammatory markers, all these characteristics together trigger the neurodegenerative process and cognitive deterioration. The etiology of AD is multifactorial, however, in recent years evidence has been shown on the significant association between dysbiosis, neuroinflammation, and neurodegeneration. In the present review, we will discuss the role of gut microbiota in the pathogenesis of AD, as well as the underlying mechanisms that trigger the use of probiotics, prebiotics, and postbiotics in neuroinflammation. Our attention will focus on the cellular and molecular mechanisms triggered by astrocytes and microglia, cells involved in mediating neuroinflammation and neurodegeneration in AD.